Sensitivity and susceptibility assessment of geological hazard factors: A case study of Xinping County in the Ailao mountain area of Yunnan Province, China - Wenli YANG; Guangshun BAI; Bin SUN; Weifeng ZHANG; Xuemei YANG (Zhongguo dizhi zaihai yu fangzhi xuebao)
In response to the selection of sensitive factors for geological disasters and susceptibility assessment, and seeking an appropriate method for evaluating the susceptibility of geological disasters in the Ailao mountain area of Yunnan Province, this paper selects Xinping County as a typical research area, with eight key factors including engineering geological rock formations, distance from fault structures, elevation, slope, slope direction, river buffer zone, roads buffer zone, and land type. The weights of evidence method based on Bayesian theory is applied to conduct a sensitivity analysis and susceptibility evaluation of geological hazard factors. The evaluation results show that the areas with high and medium susceptibility to geological disasters covering 1532.94 km2 and 2119.07 km2, respectively, with 74.06% and 24.69% of geological disaster points falling within these regions. These findings are highly consistent with the spatial distribution of historical geological disasters, proving the rationality of the chosen evaluation factors and models. This study provides valuable insights for the evaluation of geological disaster susceptibility in the Ailao mountain area of Yunnan Province.